The Antimicrobial Activity of Different Extracts from Echinophora platyloba DC. - Leili Bazvandi; Yalda Shokoohinia; Nastaran Ghiasvand; Parviz Mohajeri; Behnam Ashrafi; Iraj Salimikia* (Lorestan University of Medical Sciences, 2018)
Background and Aim: Echinophora platyloba DC (Apiaceae) is a plant endemic to Kurdistan province of Iran. Aerial part of the plant is regarded as the source of natural antimicrobial agent. Materials and Methods: The aerial part of E. platyloba was extracted with hexane, dichloromethane, acetone EtOH and EtOH: H2O respectively. The extracts were individually tested against three gram-negative (Escherichia coli, Shigella flexneri, Acinetobacter baumannii) and two gram-positive bacteria (Staphylococcus aureus, Enterococcus faecalis) via agar dilution methods. Results: The best inhibitory effect was observed in ethanolic extract, which had a remarkable inhibitory effect on all bacteria especially on S. aureus. The results also indicated that dichloromethane extract showed the weakest inhibitory effect on all types of bacteria. Meanwhile, acetone extract exhibited a relatively mild inhibitory effect. Conclusion: The antimicrobial effects of E. platyloba confirmed its potential for folk use. More comprehensive investigations are recommended concerning the significant antibacterial activity of the ethanol extract of E. platyloba to determine the exact compounds responsible for observed biological activities.